La transcendance chez Malherbe et le pouvoir de la non-identification - Quintin, Jacques (Divus Thomas, 2019)
Malherbe submits the thought of some thinkers to a hermeneutic work which consists in freeing their thoughts of dogmatic prejudices. It is a work of desacralization for the benefit of a reconfiguration of spirituality. An ethics that does not open itself to spirituality closes itself to the essential questions that liven up the human soul. The stake is to develop knowledge of human beings in favour of their freedom. It is not without consequence when we work as an ethicist which consists in clinical ethics to accompany people to make free and informed consents. Malherbe sottopone il pensiero di alcuni pensatori ad un lavoro ermeneutico che consiste nel liberare i loro pensieri dai pregiudizi dogmatici. È un lavoro di desacralizzazione a vantaggio di una riconfigurazione della spiritualità. Un’etica che non si apra alla spiritualità si chiude alle domande essenziali che ispirano l’animo umano. Si tratta di sviluppare un sapere sull’umano a favore della sua libertà. Ciò non è senza conseguenze quando si eserciti la professione di eticista che consiste, in etica clinica, nell’accompagnare le persone a prendere delle decisioni libere ed informate.